The January 25th 2011 "Revolution", 5 years later – a Balance - Habashi, Mamdouh (Argumentum, 2016)
The struggle between the rebelling masses and the old regime is the fate of every revolution in history. This rebellion has mobilized mainly the forces of the counter- revolution, both the brutal violent force, as well as the delicate strategic thinking "soft" power, which I refer to as the class brain. In the case of Egypt 2011, this struggle was very clear from the first day. The"Supreme Council of Armed Forces” (SCAF) had sacrificed Mubarak to protect or evensave the whole regime from further radicalization by the popular movement. The military leadership has indeed theatrically saluted with military honors the martyrs of the great Revolution, but at the same time they have severely resisted any claims of this movement. Every achievement was only made possible thanks to massive combat missions. Two demonstrations with more than a Million demonstrators in March 2011 were necessary to overthrow the nominee of Mubarak's cabinet. Two more followed to arrest Mubarak’s sons and his clique and bring them to tribunal in April. And for that alone to happen, this revolutionary wave had to continue with undiminished momentum until July 2011. The maxim of the SCAF was therefore; make minimal concessions towards the revolutionary forces and retain maximum of old power structures. In order for this tactic to work, the SCAF has entered into an alliance with the political power, the only force in the "class", which did in fact dispute the Mubarak regime about its share of the power, the Muslim-Brotherhood and all the other groups of political Islam.